Connecting Educators' Insights on Early Literacy with Music in Early Childhood - Simatupang, Nurhenti Dorlina; Kartika Rinakit Ade; Sri Widayati; Dewi Komalasari; Muhammad Reza (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
The low literacy rate in Indonesia requires more effective teaching methods, music as an interesting media can be a solution to address this problem. This research investigates the relationship between teachers' perceptions of music and early childhood literacy. Employing a quantitative approach with a correlational method, the study involves 1,096 early childhood education (PAUD) teachers in Banyuwangi Regency as both the subject and object of the research. Using a saturated sampling technique, the entire population of 1,096 PAUD teachers was included as the sample. Data were collected through questionnaires, which included instruments designed to measure teachers' perceptions of music and their impact on early childhood literacy. Pearson correlation analysis was utilized to analyze the data, revealing a significance value of 0.000 and a Pearson Correlation coefficient of 0.630. These results indicate a strong positive relationship between teachers' perceptions of music and early childhood literacy. The findings suggest that teachers with favorable perceptions of music are more likely to incorporate music into their teaching practices, thereby contributing to improved literacy skills among children. The latest information in this study has implications for the need to increase the integration of music as a learning medium in early childhood education (PAUD).